On convergence theory for Beltrami equations - Ryazanov, V.; Srebro, U.; Yakubov, E. (Інститут прикладної математики і механіки НАН України, 2008)
This paper is devoted to convergence theorems which play an important role in our scheme for deriving theorems on the existence of solutions of the Beltrami equations.